Analysis of Root Stumps in Middle Aged Group - Sarojini Ramya Pillay1 , Dhanraj Ganapathy2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Tooth extraction is one of the dental treatments which should be considered the last option. A decrease in thenumber of teeth may result in poor dietary habits and deterioration of quality of life. The number of extractedteeth can serve as an indicator of socio-economic and oral hygiene level. Extraction of permanent teeth isperformed for several reasons including dental caries, periodontal disease, orthodontic reasons, impactedteeth and root stumps.To assess the prevalence of root stumps in middle aged in Chennai A retrospectivecross-sectional study was conducted using the patient records from the Department of Oral maxillofacialsurgery, Saveetha Dental College, Chennai from February 2019 to February 2020, and patients who hadroot stumps were selected by nonprobability sampling. Data was collected and then subjected to statisticalanalysis.Microsoft Excel/2016 data spreadsheet was used and later exported to the Statistical Package forSocial Science for Windows (version 20.0, SPSS Inc., Chicago Ill., USA).The prevalence of root stumpswas more in males and age groups of 50-55 years showed maximum root stumps. There is no significantdifference between gender and the number of root stumps in each patient P=0.562 The study concluded thatthe prevalence of root stumps in the middle age group seems to be high when compared to other literature.Considering the limitations of this study extensive research needs to be done to find the prevalence of rootstumps in other populations and to spread awareness among the public about root stumps which are in situ.